Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Biostratigraphic and paleobiogeographic significance of two cap-shaped fossil groups from the Cambrian Xinji Formation, North China: Evidence for North China–Australia faunal links - Meng Gong; Hong Hua; Yang Hou; Xinzi Wang; Song Zhang; Zihui Wu; Xueting Wang; Ling Yu; Yan Tan; Jinzhou Luo; Lin Bai (Journal of Asian Earth Sciences, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Phosphatized heterotrophic protists from the Ediacaran–Cambrian transition in South China: New evidence for evolutionary continuity - Jinzhou Luo; Song Zhang; Xiao Min; Hong Hua; Meng Gong; Qiaokun Dai; Lin Bai; Yang Hou; Xinzi Wang; Xueting Wang; Zihui Wu (Gondwana Research, 2026)

A new biostratigraphic marker for Cambrian Stage 3 on the Northern Margin of the Yangtze Platform: Mianxiantubus–Pelagiella subangulata assemblage subzone - Xueting Wang; Hong Hua; Jinzhou Luo; Yang Hou; Meng Gong; Song Zhang; Xinzi Wang; Zihui Wu; Yan Tan; Ling Yu; Lin Bai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

CRISPR/Cas12a dual-gRNA assay enables precise detection of single-nucleotide mutations via cis-staggered-cleavage - Zhiyun Lin; Yanchi Luo; Hong Li; Baokai Shao; Xiufen Yang; Jianing Wang; Yi Wan; Fengge Song (Analytica Chimica Acta, 2026)

Semiconductor-Noble Metal Composites for Synergistic SERS Sensing and In-situ Photocatalytic Degradation Monitoring of Novel Neonicotinoid-like Pesticides - Yalin Xie; Liping Chen; Xiaoyan Huang; Wei Lin; Hong Chen; Yuanyuan Li; Xiaojun Luo; Yuanyuan Zhang (Environmental Research, 2026)

Magnetic nanohybrid with tunable electrostatic heterogeneity for integrated flow assurance and on-demand demulsification of heavy oil emulsions - Yang Xue; Shunyao Luo; Bowen Duan; Guanyu Qian; Jiahe Chen; Zuyang Liao; Zeyu Jin; Zhehao Wei; Changqing He; Hong Sui; Lin He (Journal of Hazardous Materials, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Steering catalytic pathways via nanoconfinement-tuned d-band centers in Fe clusters - Hong-Lin Zhang; An-Qi Kang; Hai-Yin Xu; Wei-Ping Xiong; Hai-Hao Peng; Yuan-Ling Luo; Mei-Ying Jia; Zhao-Hui Yang (Chemical Engineering Journal, 2026)

Mechanically robust, environment resistant, and reprocessable lignin-derived polyurethane vitrimer enabled by multi-dynamic crosslinking strategy - Wei Luo; Dengfeng Wang; Jiayang Zhao; Junze Hao; Haojie Hong; Zhihao Chen; Lin Liu; Juming Yao (Chemical Engineering Journal, 2026)

Materials-centric protein corona design in polyurethanes for pro-regenerative immune modulation and soft tissue repair - Jingjing Lin; Mingtao Luo; Haonan Qi; Xue Wu; Junhong Li; Yuan Feng; Zhen Li; Feng Luo; Jiehua Li; Hong Tan; Ting Lan; Yanchao Wang (Chemical Engineering Journal, 2026)

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

New insights into the sclerite ultrastructure and affinity of early Cambrian maikhanellids from South China - Yang Hou; Hong Hua; Jin-Zhou Luo; Meng Gong; Xin-Zi Wang; Lin Bai; Zi-Hui Wu; Xue-Ting Wang; Song Zhang (Palaeoworld, 2026)

Longitudinal trends in serum triclocarban levels from 2008 to 2018: Evidence from the prospective Dongfeng–Tongji cohort study - Caizheng Yu; Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Meian He (Environmental Research, 2026)

Corrigendum to “Catechol-induced assembly to enhance the performance of antimicrobial peptide fully” [Chem. Eng. J. Volume 524 (2025) 169195] - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Triquinane sesquiterpene octanoates from Antrodiella zonata with their cytotoxicity and antimalarial activities - Jie-Lin Yin; Qing-Shu Chen; Fang-Lu Wei; Wen-Tao Luo; Zheng-Hong Pan; Juan He (Phytochemistry, 2026)

Isolation and Cytotoxic Activities of Two New 2-Pyridone Alkaloids with Unique Structures from the Beibu Gulf Coral-Derived Acremonium sclerotigenum GXIMD 02501 - Yuning Qin; Xinjian Qu; Miaoping Lin; Hong Zhang; Huangxue Qin; Chenghai Gao; Yonghong Liu; Xuefeng Zhou; Xiaowei Luo (Journal of Ocean University of China, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Rab10 GTPase from the mud crab Scylla paramamosain is involved in the host immune response against V. parahaemolyticus infection - Chang-Hong Cheng; Hai-Peng Qin; Si-Gang Fan; Hong-Ling Ma; Guang-Xin Liu; Dong-Lin Yao; Wen-Fan Luo; Xian-Feng Yang; Zhi-Xun Guo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Synergistic regulation of calcium hydroxide and ARC microbial inoculant on rhizosphere microbiota and soil chemical properties during peanut middle growth stages in acidic red soils - Gongming Wu; Hong Yu; Ningbo Zeng; Zinan Luo; Sheng Gao; Qi Liang; Lin Li; Peiwu Li; Zemao Yang; Dengwang Liu (Rhizosphere, 2026)

Exposure trends of neonicotinoids from 2008 to 2018 and health risk in a longitudinal study in China - Jiazhen Zhang; Hong Guo; Lin Liu; Jinglan Ma; Jiao Zou; Zhengyang Xiao; Zhewen Li; Yunqi Luo; Caizheng Yu; Meian He (Environmental Research, 2026)

Lecithin supplementation to HFD improves largemouth bass liver health: Implications for regulating lipid homeostasis, antioxidant responses and endoplasmic reticulum stress - Biao Wang; Hua Zheng; Juan Xiong; Hong-Jun Yang; Qing-Lin Li; Zhi Luo (Fish Physiology and Biochemistry, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

A new model for the global patterning of spores and pollen grains - Kun L. Yang; Zhu L. Yang; Yang Luo; Jia Y. Lin; Hong Wang; Pan Meng Wang (Protoplasma, 2026)

Investigating the application of 3D skin models in micronucleus assay and comet assay - Tianyin Lin; Huan Luo; Jingqiu Sun; Chen Dong; Xinyu Hong; Ping Xiao; Gonghua Tao (Toxicology Letters, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

Smoldering heterogeneous oily sludge: Key influencing factors - Yi Lin; Zehua Luo; Fuli Li; Chih-Huang Weng; Yanru Hao; Na Liu; Mei Hong (Journal of Cleaner Production, 2025)

Catechol-induced assembly to enhance the performance of antimicrobial peptide fully - Xiao Wang; Yuanyuan He; Beibei Cui; Yuan Feng; Jingjing Lin; Xirui Long; Yanchao Wang; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Breaking the monopoly of the Zn(002): Phosphoryl-heterocyclic co-adsorption to promote preferential exposure of Zn(101) crystal plane for dendrite-free Zn metal anodes - Haoran Lang; Chao Li; Jingxin Zhao; Chunyuan Xiong; Lieyuan Zhang; Yijia Luo; Qiaoji Zheng; Xin Tan; Hong Fu; Bingang Xu; Dunmin Lin (Chemical Engineering Journal, 2025)

Biodegradable polyurethane-decellular extracellular matrix based bioscaffolds promote nerve repair after spinal cord injury - Mingtao Luo; Jingjing Lin; Junhong Li; Min He; Huanrui Hu; Xiao Wang; Jiehua Li; Cong Wu; Lu Ma; Yanchao Wang; Hong Tan (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

Actin–myosin complex dissociation initiates programmed cell death during cold storage of grass carp muscle - Xin Xiong; Huijuan Zhang; Lin Chen; Peipei Dou; Tianzhuo Huang; Shuai Zhuang; Yuqing Tan; Huawei Ma; Hui Hong; Yongkang Luo (Food Research International, 2025)

Machine learning-assisted dual-mode hydrogel sensor for the detection of nitrite - Si-Qi Yang; Bao-Zhu Jia; Jie Liu; Fan-Xuan Gong; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Multiple endogenous aldehydes amplify acetaminophen-induced liver injury - Hong Pan; Qi Luo; Qiuyi Jing; Lin Chen; Ni Li; Chao Fang; Fuguo Shi (Chemico-Biological Interactions, 2025)

Lignicolous freshwater fungi from karst landforms in China: Introducing Wongia guttulata sp. nov. associated with bamboo - Wen-Peng Wang; Hong-Wei Shen; Xi-Jun Su; Lin Yang; Zhong-Yuan Zhang; Zong-Long Luo (Mycological Progress, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Crosstalk between mitochondrial dysfunction and endoplasmic reticulum stress in apoptosis: Implications for grass carp flesh quality during cold storage - Xin Xiong; Qing Li; Lin Chen; Shuai Zhuang; Yuqing Tan; Hui Hong; Yongkang Luo (Food Chemistry, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Environmental adversity, endoplasmic reticulum stress, and neurogenesis - Zuohui Zhang; Wen Wen; Di Hu; Hui Li; Hong Lin; Jia Luo (NeuroToxicology, 2025)

Turbo Equalization Based on a Virtual Decoder for Underwater Acoustic Communication - Cong Peng; Lei Wang; Lerong Hong; Zehua Lin; An Luo (Journal of Marine Science and Engineering, 2025)
By transferring external information between the equalizer and the decoder iteratively, the performance of turbo equalization is close to the channel capacity. Conventional turbo equalization (CTE) relies on channel coding, while the transmission of external information is a problem in an uncoded system, and turbo equalization without channel coding (TECC) remains unexplored. Therefore, this paper introduces a TECC framework with a virtual decoder constructed by bidirectional processing. The main innovation is that the existence of the virtual decoder enables the transmission of external information. Under this new framework, we implement it with a minimum mean square error decision feedback equalizer (MMSE-DFE) and evaluate its performance across stationary channels and multipath fading channels. Simulation results demonstrate significant communication performance enhancement after three to four iterations, surpassing both conventional bidirectional and unidirectional equalization. In addition, the proposed TECC is verified through underwater acoustic communication in a sea trial. The results also demonstrate that the TECC achieves better bit error performance.

Antibacterial antioxidant polyurethane/curcumin patch with anti-swelling ability for tissue adhesion and treatment of oral ulcers - Xiaolei Guo; Lin Yang; Nan Sheng; Xirui Long; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Exploring the effect of low-temperature thermal-alkaline pretreatment on struvite recovery from metals-phosphorus rich sludge - Lin Wei; Junjie Ji; Tianqiu Hong; Yugang Dong; Qiang Zhang; Lei Luo; Ruolan Li; Ziyue Li; Yiming Tang (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Cumulus cells and the TNF-alpha signaling facilitate aging of ovine oocytes - Shuai Gong; Yan Zhang; Chao-Qun Cong; Guo-Liang Wang; Lin Jiang; Hong-Jie Yuan; Jing-He Tan; Ming-Jiu Luo (Theriogenology, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Research on LSTM-PPO Obstacle Avoidance Algorithm and Training Environment for Unmanned Surface Vehicles - Wangbin Luo; Xiang Wang; Fang Han; Zhiguo Zhou; Junyu Cai; Lin Zeng; Hong Chen; Jiawei Chen; Xuehua Zhou (Journal of Marine Science and Engineering, 2025)
The current unmanned surface vehicle (USV) intelligent obstacle avoidance algorithm based on deep reinforcement learning usually adopts the mass point model to train in an ideal environment. However, in actual navigation, due to the influence of the ship model and the water surface environment, the training set is triggered. The reward function does not match the actual situation, resulting in a poor obstacle avoidance effect. In response to the above problems, this paper proposes a long and short memory network-proximal strategy optimization (LSTM-PPO) intelligent obstacle avoidance algorithm for non-particle models in non-ideal environments, and designs a corresponding deep reinforcement learning training environment. We integrate the motion characteristics of the unmanned boat and the influencing factors of the surface environment, based on the curiosity-driven set reward function, to improve its autonomous obstacle avoidance ability, combined with the LSTM network to identify and save obstacle information to improve the adaptability to the unknown environment; virtual simulation is performed in Unity. The engine builds a USV physical model and a refined water deep reinforcement learning training environment including a variety of obstacle models. The experimental results demonstrate that the LSTM-PPO algorithm exhibits an effective and rational obstacle avoidance effect, with a success rate of 86.7%, an average path length of 198.52 m, and a convergence time of 1.5 h. A comparison with the performance of three other deep reinforcement learning algorithms reveals that the LSTM-PPO algorithm exhibits a 21.5% reduction in average convergence time, an 18.5% reduction in average path length, and an approximately 20% enhancement in the success rate of obstacle avoidance in complex environments. These results indicate that the LSTM-PPO algorithm can effectively enhance the search efficiency and optimize the path planning in obstacle avoidance for unmanned boats, rendering it more rational.

Acidosis induces autophagic cell death through ASIC1-mediated Akt/mTOR signaling in HT22 neurons - Miao Guo; Ming-Yue Qiu; Lin Zeng; Ya-Xiong Nie; Ya-Ling Tang; Yan Luo; Hong-Feng Gu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Corrigendum to “Cobalt induces neurodegenerative damages through Pin1 inactivation in mice and human neuroglioma cells” [J Hazard Mater 419 (2021) 126378] - Fuli Zheng; Yuqing Li; Fengshun Zhang; Yi Sun; Chunyan Zheng; Zhousong Luo; Yuan-Liang Wang; Michael Aschner; Hong Zheng; Liqiong Lin; Ping Cai; Wenya Shao; et al. (Journal of Hazardous Materials, 2025)

Nanozyme-mediated ratiometric fluorescence hydrogel for on-site detection of sulfite in food - Si-Qi Yang; Bao-Zhu Jia; Jie Liu; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Cinnamic acid application inhibits the browning of cold-stored taro slices by maintaining membrane function, reducing flavonoid biosynthesis and enhancing glutathione metabolism - Yukun Wang; Hong Ye; Wei Lin; Guang Wang; Tao Luo; Jinming He; Bin Wang (Postharvest Biology and Technology, 2024)

New Ediacaran tubular fossils from southern Shaanxi, China - Qiao-Kun Dai; Hong Hua; Jin-Zhou Luo; Xiao Min; Xiao-Qiang Pan; Zi-Wei Liu; Song Zhang; Lin Bai (Palaeoworld, 2024)

Complementarity and competitive trade-offs enhance forage productivity, nutritive balance, land and water use, and economics in legume-grass intercropping - Chong Liang Luo; Hai Xia Duan; Ya Lin Wang; Hong Jin Liu; Shi Xiao Xu (Field Crops Research, 2024)

Ratiometric fluorescence and photothermal dual-mode immunosensor based on MnO2 nanosheets for the detection of isocarbophos - Jie Liu; Hao Deng; Bao-Zhu Jia; Ze-Shan Lin; Yu Wang; Hong Wang; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2024)

Electricity production and nutrient recovery from waste activated sludge via microbial fuel cell and subsequent struvite crystallization: Effect of low temperature thermo-alkaline pretreatment - Lin Wei; Ziyue Li; Tianqiu Hong; Qiang Zhang; Lei Luo; Yiming Tang; Junjie Ji; Jianyu Kong; Xiaoke Ding (Bioresource Technology, 2024)

Protective Role of (-)-Epicatechin on Trimethylamine-N-Oxide (TMAO)-Induced Cardiac Hypertrophy via SP1/SIRT1/SUMO1 Signaling Pathway - Siting Hong; Jing Lu; Jiaoyan Li; Yingchun Luo; Dongxue Liu; Yuanyuan Jin; Zeng Wang; Yibo Wang; Hao Zhang; Xin Zhang; Yang Li; Haoruo Zhang; et al. (Cardiovascular Toxicology, 2024)

Deep-sea microplastics aging and migration exerted by seamount topography and biotopes in the subtropic Northwest Pacific Ocean - Huige Guo; Xiaochen Wang; Hong Cheng; Zhaohe Luo; Jieliang Huang; Hongzhe Chen; Jinling Pang; Kunning Lin; Shuyuan Huang; Xuhui Zhang; Yuanbiao Zhang (Science of The Total Environment, 2024)

Insight into electricity production performance from dried waste activated sludge in dual chamber microbial fuel cells: Influencing factors, neural network modelling and microbial community analysis - Lin Wei; Ziyue Li; Tianqiu Hong; Yiming Tang; Ying Ge; Dongdong Ji; Qiang Zhang; Lei Luo; Jianyu Kong; Xiaoke Ding (Journal of Environmental Chemical Engineering, 2024)

From texture to structure: The key role of caspase-3 on grass carp myofibrillar protein during postmortem storage - Xin Xiong; Huijuan Zhang; Shuai Zhuang; Kai Wang; Ning Ding; Hui Hong; Lin Chen; Yuqing Tan; Yongkang Luo (Food Bioscience, 2024)

Caspase-3 interactions with calpain and cathepsin L: Implications for protein stability and quality in fish fillets during postmortem storage - Xiong Xin; Ding Ning; Zhuang Shuai; Dou Peipei; Feng Ruifang; Tan Yuqing; Ma Huawei; Chen Lin; Hong Hui; Luo Yongkang (Food Bioscience, 2024)

Analysis of factors affecting the prefabricated housing promotion from the perspective of stakeholders - Zezhou Wu; Shenghan Li; Yuhan Lin; Lirong Luo; Hong Xue; Maxwell Fordjour Antwi-Afari (Energy and Buildings, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Purification of inorganic nitrogen from the mariculture tail water by anaerobic/anoxic/oxic (A2O) process - Shuangcheng Jiang; Jinkun Yang; Chunshan Wu; Hong Du; Huidong Zheng; Qi Lin; Wentao Pan; Chongming Zhong; Kaiwen Tan; Feng Lin; Zhuhua Luo; Zhong Pan; et al. (Marine Pollution Bulletin, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Arsenic effectively improves the degradation of fluorene by Rhodococcus sp. 2021 under the combined pollution of arsenic and fluorene - Hong-Peng Shi; Ying-Hao Zhao; Mei-Lin Zheng; Cheng-Yan Gong; Lei Yan; Ying Liu; Yong-Ming Luo; Zhi-Pei Liu (Chemosphere, 2024)

A new silicified microfossil assemblage from the Ediacaran Dengying Formation in South Shaanxi, China - Qiaokun Dai; Hong Hua; Jinzhou Luo; Xiao Min; Ziwei Liu; Song Zhang; Meng Gong; Lin Bai (Precambrian Research, 2024)

Isolation and absolute configuration of alkylpyridine alkaloids from the marine sponge Hippospongia lachne - Dong-Xue Fan; Xiang-Chao Luo; Ya-Fang Ding; Li-Yun Liu; Xin Wang; Jia-Yan Pan; Yuan-Yuan Ji; Jie Wang; Cui Li; Li-Li Hong; Hou-Wen Lin (Phytochemistry, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Role of covalent modification by hepatic aldehydes in dictamnine-induced liver injury - Qi Luo; Yang Shen; Guohong Zhai; Lin Chen; Furong Ou; Luxi Yi; Danli Yang; Hong Pan; Fuguo Shi (Toxicology Letters, 2024)

Effective photocatalytic inactivation of Microcystis aeruginosa by Ag3VO4/BiVO4 heterojunction under visible light - Gongduan Fan; Qiuan Lin; Jiuhong Lin; Mingqian Xia; Shoubin Chen; Jing Luo; Jianyong Zou; Zhanglin Hong; Kaiqin Xu (Chemosphere, 2024)

Reconstruction of microcontinents during the assembly of Rodinia: A case study from the Central Tianshan Block - Lin-Xi Wang; Hu Huang; Ming-Cai Hou; Benjamin Kneller; Fu-Hao Xiong; Hong-Wei Luo; Sheng-Xian Zhu (Precambrian Research, 2024)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Rapid Genotyping of Campylobacter coli Strains from Poultry Meat by PFGE, Sau-PCR, and fla-DGGE - Ge-Feng Yao; Yi-Lin Hu; Nian-Qing Kong; Jin-Hong Liu; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Current Microbiology, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

Controllable formation of polydopamine on carbon dots for ultrasensitive detection of alkaline phosphatase and ratiometric fluorescence immunoassay of benzocaine - Shi-Qi Lin; Bao-Zhu Jia; Wei Luo; Hong Wang; Hong-Tao Lei; Wen-Feng Zhang; Zhen-Lin Xu; Lin Luo (Food Chemistry, 2023)

Immune-microenvironment modulatory polyurethane-hyaluronic acid hybrid hydrogel scaffolds for diabetic wound treatment - Yuan Feng; Kecen Xiao; Jinlin Chen; Jingjing Lin; Yuanyuan He; Xueling He; Fuyi Cheng; Zhen Li; Jiehua Li; Feng Luo; Hong Tan; Qiang Fu (Carbohydrate Polymers, 2023)

Dual application of Tribonema sp. GXU-A10 for purifying molasses vinasse and promoting the growth and health of Oreochromis niloticus - Hong-Yu Deng; Yue-Xin Sun; Xin-Qiang Chen; Yu Jiang; Wan-Lin Gu; Luo-Dong Huang; Pei-Hong Shen (Algal Research, 2023)

Organophosphate diesters (DAPs) and hydroxylated organophosphate flame retardants (HO-OPFRs) as biomarkers of OPFR contamination in a typical freshwater food chain - Yin-E Liu; Xiao-Jun Luo; Hong-Chang Ding; Lin Qi; Bin Tang; Bi-Xian Mai; Giulia Poma; Adrian Covaci (Chemosphere, 2023)

A bispecific nanobody with high sensitivity/efficiency for simultaneous determination of carbaryl and its metabolite 1-naphthol in the soil and rice samples - Min-ling Liu; Zi-jian Chen; Xiao-qing Huang; Hong Wang; Jin-li Zhao; Yu-dong Shen; Lin Luo; Xiao-wei Wen; Bruce Hammock; Zhen-lin Xu (Environmental Pollution, 2023)

Electronic regulation and hydrophobicity improvement of the palladium active site by ionic liquid to achieve high selectivity direct synthesis of hydrogen peroxide - Lang Wu; Hong Qin; Songhua Zhou; Ziming Luo; Yang Xiao; Huan You; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Response Surface Methodology and Artificial Neural Network Modeling for the Removal of Volatile Organic Compounds in Biotrickling Filters - Tianqiu Hong; Lin Wei; Kangping Cui; Yugang Dong; Lei Luo; Tingting Zhang; Ruolan Li; Ziyue Li; Yiming Tang (Water, Air, & Soil Pollution, 2023)

Transient neonatal hyperglycemia induces metabolic shifts in the rat hippocampus: a 1H NMR-based metabolomics analysis - Yinli Huang; Junli Chen; Jiahui Lu; Hanqi Luo; Na Ying; Wei Dong; Minjie Lin; Hong Zheng (Metabolic Brain Disease, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Self-assembled synthesis of Pd/SPEn from polyelectrolyte membranes for efficient direct synthesis of H2O2 via inhibiting the dissociation of O − O bond - Entong Ye; Zheng Chen; Yongyong Shi; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Quansheng Wu; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Revealing and quantifying the effect of cattiite coprecipitation on the purity of K-struvite in aqueous solution - Lin Wei; Tingting Zhang; Tianqiu Hong; Yugang Dong; Dongdong Ji; Lei Luo; Ruolan Li; Ziyue Li; Yiming Tang (Journal of Environmental Chemical Engineering, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Biosensors for detection of paralytic shellfish toxins: Recognition elements and transduction technologies - Liu-Na Wei; Lin Luo; Bing-Zhi Wang; Hong-Tao Lei; Tian Guan; Yu-Dong Shen; Hong Wang; Zhen-Lin Xu (Trends in Food Science & Technology, 2023)

Swallowtail butterflies and hawkmoths contribute equally to the pollination of Habenaria dentata (Orchidaceae) - Shao-Lin Tan; Xing-Hui Chen; Hai-Hong Liao; Lang Huang; Han-Wen Xiao; Huo-Lin Luo; Dong-Jin Xiong; Bo-Yun Yang; Zong-Xin Ren (Flora, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Photocurable liquid crystal hydrogels with different chargeability and tunable viscoelasticity based on chitin whiskers - Jingsheng Chen; Zelin Zhu; Jiaqing Chen; Yiting Luo; Lin Li; Kun Liu; Shan Ding; Hong Li; Mingxian Liu; Changren Zhou; Binghong Luo (Carbohydrate Polymers, 2023)

Sharply and simultaneously increasing pollutant accumulations in cells of organisms induced by rare earth elements in the environment of Nanjing - Qing Yang; Mengzhu Cheng; Qing Zhou; Lihong Wang; Yunlong Jiao; Yongqiang Liu; Shuya Zhang; Li Tan; Zhenhong Gu; Hong Zhu; Hongli Luo; Daozhe Lin; et al. (Chemosphere, 2023)

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Bile acids and their receptors in regulation of gut health and diseases - Sen Lin; Sutian Wang; Peng Wang; Cuiming Tang; Zhenjiang Wang; Lian Chen; Guoqing Luo; Hong Chen; Yuntao Liu; Bin Feng; De Wu; Douglas G. Burrin; et al. (Progress in Lipid Research, 2023)

Innate and Adaptive Immune Responses Induced by Aspergillus fumigatus Conidia and Hyphae - Yingzhi Luo; Fang Liu; Lin Deng; Jie Xu; Qingtao Kong; Yi Shi; Hong Sang (Current Microbiology, 2023)

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

Nonlinearity of Subtidal Estuarine Circulation in the Pearl River Estuary, China - Hongzhou Xu; Jian Shen; Dongxiao Wang; Lin Luo; Bo Hong (Frontiers in Marine Science, 2021)
The Pearl River Estuary (PRE) is a bell-shaped estuary with a narrow deep channel and wide shoals. This unique topographic feature leads to different dynamics of the subtidal estuarine circulation (SEC) in the PRE compared with a narrow and straight estuary. In this study, the nonlinear dynamics of the SEC in the PRE under mean circumstance are analyzed by using a validated 3D numerical model. Model results show that the nonlinear advections reach leading order in the along-channel momentum balance. Modulated by tide, the nonlinear advections show significant temporal variations as they have much larger values during spring tide than that during neap tide. Unlike straight and narrow estuaries, both tidally and cross-sectionally averaged axial and lateral advections play important roles in driving the SEC in the PRE in which the axial advection dominates the nonlinear effect, but the two nonlinear terms balance each other largely resulting in a reduced nonlinear effect. Despite this, the total nonlinear advection is still comparable with other terms, and it acts as the baroclinic pressure to reinforce the SEC, especially during the ebb tide, suggesting a flood–ebb asymmetry of the nonlinear dynamics in the PRE. In addition, diagnostic analyses of the along-channel vorticity budget show that nonlinear advections also make significant contribution to drive the lateral circulation in the PRE as Coriolis and baroclinic pressure terms, indicating complex dynamics of the circulation in the PRE.

The response to flooding of two overwintering rice stem borers likely accounts for their changing impacts - Guang-Hua Luo; Zhi-Xin Luo; Zhi-Ling Zhang; Yang Sun; Ming-Hong Lu; Zhao-Lin Shu; Zi-Hua Tian; Ary A. Hoffmann; Ji-Chao Fang (Journal of Pest Science, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Multifunctional Role of Polyvinylpyrrolidone in Pharmaceutical Formulations - Yu Luo; Yanlong Hong; Lan Shen; Fei Wu; Xiao Lin (AAPS PharmSciTech, 2021)

Production of gene-edited pigs harboring orthologous human mutations via double cutting by CRISPR/Cas9 with long single-stranded DNAs as homology-directed repair templates by zygote injection - Fei Xie; Xiaoyang Zhou; Tingting Lin; Lulu Wang; Chuanhong Liu; Xi Luo; Lihua Luo; Huayu Chen; Kenan Guo; Hong Wei; Yong Wang (Transgenic Research, 2020)

Streptomyces taklimakanensis sp. nov., an actinomycete isolated from the Taklimakan desert - Lin-Lin Yuan; Li-Li Zhang; Xiao-Xia Luo; Zhan-Feng Xia; Bei-Bei Sun; Hong Zeng (Antonie van Leeuwenhoek, 2020)

Regulation of mitochondrial NAD pool via NAD+ transporter 2 is essential for matrix NADH homeostasis and ROS production in Arabidopsis - Lilan Luo; Yajun He; Yannan Zhao; Qian Xu; Jian Wu; Haiyan Ma; Hongyan Guo; Lin Bai; Jianru Zuo; Jian-Min Zhou; Hong Yu; Jiayang Li (Science China Life Sciences, 2019)

Correction to: Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Antidepressant-Like Action of Single Facial Injection of Botulinum Neurotoxin A is Associated with Augmented 5-HT Levels and BDNF/ERK/CREB Pathways in Mouse Brain - Yang Li; Jing Liu; Xu Liu; Cun-Jin Su; Qi-Lin Zhang; Zhi-Hong Wang; Lei-Fang Cao; Xue-Yan Guo; Ya Huang; Weifeng Luo; Tong Liu (Neuroscience Bulletin, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

Neuroligins Differentially Mediate Subtype-Specific Synapse Formation in Pyramidal Neurons and Interneurons - Qiang-Qiang Xia; Jing Xu; Tai-Lin Liao; Jie Yu; Lei Shi; Jun Xia; Jian-Hong Luo; Junyu Xu (Neuroscience Bulletin, 2019)

Mechanistic studies of the apoptosis induced by the macrocyclic natural product tetrandrine in MGC 803 cells - Sai-Qi Wang; Hong-Lin Hou; Liang-Yu Bie; Cai-Yun Nie; Luo-Nan Wang; Shaobing Gao; Ting-Ting Hu; Xiao-Bing Chen (Medicinal Chemistry Research, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

Protective effects of paeonol on inflammatory response in IL-1β-induced human fibroblast-like synoviocytes and rheumatoid arthritis progression via modulating NF-κB pathway - Ke-feng Zhai; Hong Duan; Lin Luo; Wen-gen Cao; Fang-kai Han; Ling-ling Shan; Xue-mei Fang (Inflammopharmacology, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

A new piperidine alkaloid from the leaves of Microcos paniculata L. - Gang Zhang; Na Zhang; Li Xu; Hong-Tan Wu; Dan Chen; Qi-Huang Lin; Lian-Zhong Luo (Natural Product Research, 2017)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The substrate promiscuity of a phosphopantetheinyl transferase SchPPT for coenzyme A derivatives and acyl carrier proteins - Yue-Yue Wang; Hong-Dou Luo; Xiao-Sheng Zhang; Tao Lin; Hui Jiang; Yong-Quan Li (Archives of Microbiology, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Spectroscopic characterization of the complexes between Fe/Mn and natural organic matters by electron paramagnetic resonance and synchrotron-based techniques - Hong-Wei Luo; Zhi-Qi Lin; Guo-Ping Sheng (Ecotoxicology, 2015)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Overexpression of Glycine soja WRKY20 enhances both drought and salt tolerance in transgenic alfalfa (Medicago sativa L.) - Lili Tang; Hua Cai; Hong Zhai; Xiao Luo; Zhenyu Wang; Lin Cui; Xi Bai (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Notch inhibition promotes fetal liver stem/progenitor cells differentiation into hepatocytes via the inhibition of HNF-1β - Tao Wang; Tao Chen; Hong-yin Liang; Hong-tao Yan; Ning Lin; Li-ye Liu; Hao Luo; Zhu Huang; Nan-lin Li; Wei-hui Liu; Li-jun Tang (Cell and Tissue Research, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

HIRA is essential for the development of gibel carp - Meng-Yu Wang; Qiu-Hong Guo; Xin-Zheng Du; Li Zhou; Qian Luo; Qiao-Hui Zeng; Jia-Lin Wang; Hao-Bin Zhao; Yu-Feng Wang (Fish Physiology and Biochemistry, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Different Binding Affinities of Pb2+ and Cu2+ to Glycosylation Variants of Human Serum Transferrin Interfere with the Detection of Carbohydrate-Deficient Transferrin - Lian-Zhong Luo; Hong-Wei Jin; Lin Huang; He-Qing Huang (Biological Trace Element Research, 2011)

Effect of perinatal thyroid hormone deficiency on expression of rat hippocampal conventional protein kinase C isozymes - Hong-Mei Zhang; Ning Lin; Yan Dong; Qing Su; Min Luo (Molecular and Cellular Biochemistry, 2011)

Potential Challenges of Climate Change to Orchid Conservation in a Wild Orchid Hotspot in Southwestern China - Hong Liu; Chang-Lin Feng; Yi-Bo Luo; Bao-Shan Chen; Zhong-Sheng Wang; Hong-Ya Gu (The Botanical Review, 2010)

Evidence for the Formation of the Male Gynogenetic Fish - Shaojun Liu; Qinbo Qin; Yuequn Wang; Hong Zhang; Rurong Zhao; Chun Zhang; Jing Wang; Wei Li; Lin Chen; Jun Xiao; Kaikun Luo; Min Tao; et al. (Marine Biotechnology, 2010)

Phylogenetic analysis of Mycoplasma suis isolates based on 16S rRNA gene sequence in China - Rong-Qiong Zhou; Kui Nie; Han-Cheng Huang; Shi-jun Hu; Zuo-yong Zhou; Hong-Lin Luo (Veterinary Research Communications, 2009)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Identification of estrogen-responsive genes in chick liver - Yunfeng Zhu; Mei Wang; Hong Lin; Zheng Li; Jia Luo (Cell and Tissue Research, 2001)